2001
DOI: 10.1007/s005340100013
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous resection of pancreas and liver metastases from different metachronous primary cancers

Abstract: Resection of a pancreatic head tumor and partial resection of the liver for metastatic lesions were carried out simultaneously in a 72-year-old woman. The patient had a history of two previous operations, right nephrectomy for renal cell carcinoma (clear cell type), done 14 years previously, and an Autincloss procedure for cancer of the left breast (solid tubular carcinoma); (T1N0M0; stage I) done 7 years previously. At the current presentation, preoperative radiographic examination showed a hypervascular tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…A total of 411 patients who underwent resection of pancreatic RCC metastases were described in 170 articles1, 2, 5–7, 14–178. Data for individual patients were not provided in ten reports containing a total of 100 patients27, 29, 63, 68, 75, 113, 119, 122, 159, 176.…”
Section: Methodsmentioning
confidence: 99%
“…A total of 411 patients who underwent resection of pancreatic RCC metastases were described in 170 articles1, 2, 5–7, 14–178. Data for individual patients were not provided in ten reports containing a total of 100 patients27, 29, 63, 68, 75, 113, 119, 122, 159, 176.…”
Section: Methodsmentioning
confidence: 99%
“…PIP has also been used to discriminate between primary tumors of ovary, breast, and colon [107]. In another study, [108] PIP showed metastasis in renal cell carcinoma, pancreatic carcinoma and the liver tumor along with breast cancer. Immunohistochemical analysis showed the over-expression of PIP in adenocarcinoma of the brain [109] and lung adenocarcinoma [92, 94, 110 -112].…”
Section: Tumor Progression and Biomarkermentioning
confidence: 95%